New records of seven seaweeds from the St. Martin’s Island, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2025)
The present paper deals with seven seaweeds taxa namely,  Blidingia minima (Kützing) Kylin,  Bryopsis pennata Lamouroux  and Halimeda simulans Howe from Chlorophyceae; Dictyopteris plagiogramma (Montagne) Vickers and Padina perindusiata Thivy from Phaeophyceae and Galaxaura obtusata (Ellis & Solander) Lamouroux and Liagora valida Harvey  from  Rhodophyceae have been identified, described, and illustrated as new records for Bangladesh. Of these, Blidingia is also a new generic record for Bangladesh.Bangladesh J. Plant Taxon. 32(1): 77-82, 2025 (June)